The anti-skin-aging effect of oral administration of gelatin from the swim bladder of Amur sturgeon (Acipenser schrenckii). Issue 7 (12th June 2019) - Wang, Lin; Wang, Xiaoxiao; Bai, Fan; Fang, Yong; Wang, Jinlin; Gao, Ruichang
Abstract : Gelatin was extracted from the swim bladder of Amur sturgeon with hot water at 50 °C with acceptable yield (76.54%) and it showed and type I collagen features. Abstract : Gelatin was extracted from the swim bladder of Amur sturgeon with hot water at 50 °C with acceptable yield (76.54%) and it showed type I collagen features. The degree of hydrolysis reached 70.42%, and 26.55% of collagen peptides (380.76 Da) survived, after simulating digestion, absorption and peripheral blood circulation in vitro . In situ single-pass intestinal perfusion showed that the AMW of the collagen peptides was about 1100 Da in the intestine and they were mainly absorbed in the jejunum (61.11%). A 12-month feeding experiment using rats demonstrated that gelatin improved the histological structure, increased the thickness of the dermis (18.45%) and the density of collagen fibers (22.17%), and decreased the ratio of type III to type I collagen (43.44%) of chronologically aged skin at 3.85 g per kg bw per d. Moreover, the antioxidant enzyme activities in skin were significantly enhanced, while the malondialdehyde content was reduced by 31.99%. These results provided new insights into the development of new nutraceuticals and functional foods for the anti-skin-aging effect.